The Oxford companion to military history - Holmes, Richard, 1946-2011.; Strachan, Hew.; Bellamy, Chris; Bicheno, Hugh. (Oxford ; New York : Oxford University Press, 2001)
"This Oxford companion does much to untangle the long and complicated history of military events in Europe and North America since the 18th century. The thoughtful entries are clear, concise, and readable, with a number of extended entries on such subjects as artillery, infantry, and the science and technology of war."--"Outstanding Reference Sources," American Libraries, May 2002.
Includes bibliographical references and index.
Keywords: Military history